The Impact of TikTok Marketing Strategy on Purchase Intention Through Brand Image: A Case Study of N’Pure - Rifki Febrian; Rah Utami Nugrahani (Dinasti Publisher, 2025)
The beauty industry in Indonesia has grown rapidly, driven by the increasing popularity of local skincare brands. One such brand, N’Pure, leverages TikTok to engage with consumers through interactive content, hashtags, live sessions, and campaigns. Social media marketing is now considered a highly effective approach to reach and influence consumer behavior. However, N’Pure faces challenges, including intense price competition from imported products and reduced consumer purchasing power, which leads to more selective buying decisions. This study investigates the influence of social media marketing on purchase intention, with brand image as a mediating variable. A quantitative, causal approach was employed using a sample of 400 respondents selected through purposive sampling. Data were collected via an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Findings reveal that social media marketing has a positive and significant effect on purchase intention, both directly and indirectly through brand image. Social media marketing also significantly enhances brand image, and brand image itself has a positive impact on purchase intention. These results highlight the strategic role of TikTok-based marketing in shaping brand perception and driving consumer purchase behavior in the skincare industry.